Tourist lifestyle: Food and travel activities at a gastronomy destination in Türkiye through the mediating role of destination familiarity - Kement, Uzeyir; Göral, Murat; Bayatkara, Yusuf; Durmaz, Yakup; Erkol Bayram, Gül (Turyzm/Tourism, 2024)
This work aims to determine the effect of the travel preferences of domestic and foreign tourists visiting Gaziantep province in Türkiye and their participation in destination food and travel activities, as well as examining the mediating role of destination familiarity. The research model includes three sub-factors for travel lifestyle: preference for proximity and comfort, interest in new and local culture, and preference for activities and adventures. While preference for destination food activities has two sub-factors: interest in food activities and tasting local flavors. Additionally, destination familiarity and preference for destination travel activities are the measures used in the research model. The research sample consists of domestic and foreign tourists visiting Gaziantep between March and April 2022; 418 questionnaires were filled in by participants chosen by random sampling. Data analysis was made using SPSS and SmartPLS. As reflective and formative scales were used together in the data analysis, the partial least squares method (PLS-SEM) was used. The research results suggest that preference for proximity and comfort, interest in new and local culture, preference for activities and adventures, and destination familiarity have a positive significant effect on interest in food activities. While interest in the new and local culture and preference for activities and adventures, have a positive significant effect on tasting local flavors; preference for proximity and comfort and destination familiarity do not have such an effect. It was also found that preference for proximity and comfort, interest in the new and local culture, preference for activities and adventures, and destination familiarity have a positive and significant effect on preferences for destination travel activities. Lastly, interest in new and local culture and preference for activities and adventures have a positive significant effect on destination familiarity while preference for proximity and comfort do not.